Factors Influencing MNCs’ Location Decision - Mai, Nguyen Thi Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
The significant growth of international investment in recent decades has led to the creation of a number of theoretical schools explaining this phenomenon and trying to answer the question of why multinational companies (MNCs) choose to locate their foreign direct investment (FDI) at one location not others? What are other factors influencing that choice? Research in this area is derived from two intertwin tradditions: the first is derived from the trade theory and economics of industrial organization and the second is the internationalization process approach associated with Uppsala model. However, both approaches have limitations and important bias. The paper will review these two approaches, analyze and identify the limitations of each approach, and give some suggestions for future research.